Certification markers for empirical quantification of post-consumer recycled content in extruded polyethylene film. (February 2018) - Curtzwiler, Greg W.; Williams, Eric B.; Hurban, Emily; Greene, Joseph; Vorst, Keith L.
Abstract: High-density polyethylene is an important polymer for a variety of industrial applications. The pressure for landfill diversion strategies have increased with consumer awareness of traditional end-of-life practices. It is critical to understand the influence of post-consumer recycled polymer (PCR) content on properties and consumer safety as converters blend PCR with virgin resin to increase sustainability. The ability to empirically quantify the PCR content is vital for compliance with minimum content laws. This work determined ∼380% increase in UVA absorption, increased carbonyl and terminal vinyl functional groups, a 50% reduction of fluorescence properties, a reduction of the polymer crystal quality, and a ∼4 °C increase in the degradation temperature. The extractables content of all PCR blends complied with the Code of Federal Regulations for direct food contact applications. Trends between the measured properties and PCR content identified potential certification markers for empirical quantification of PCR content and single-measurement quality control metrics. Highlights: The pressure for landfill diversion strategies of post-consumer waste have increased. The influence of post-consumer recycled polymer (PCR) on properties was measured. Empirical quantification of PCR content is vital for minimum content law compliance. All PCR blends can be utilized for direct food contact applications. Potential certification markers for empirical PCR quantification were determined.